Phil Spector - Pacino, Al 1940-; Mirren, Helen 1945-; Tambor, Jeffrey 1944-; Ejiofor, Chiwetel 1977-; Pidgeon, Rebecca 1965-
Academy Award winners Al Pacino and Helen Mirren star in this production written and directed by Pulitzer Prize-winning and Oscar-nominated playwright David Mamet. An exploration of the client-attorney relationship between legendary music producer Phil Spector and defense attorney Linda Kenney Baden, who represented Spector during his first trial for murder
Special Feature: Writer/director David Mamet an dstars Al Pacino and Helen Mirren discuss making the film
Originally broadcast on television as a made-for-TV movie by HBO in 2013
Keywords: Fernsehfilm; Spector, Phil / 1939-2021 / Drama; Baden, Linda Kenney / 1953- / Drama; Clarkson, Lana / Drama; Sound recording executives and producers / Drama; Criminal defense lawyers / Drama; Trials (Murder) / Drama; Baden, Linda Kenney / 1953-; Clarkson, Lana; Spector, Phil / 1939-2021; Criminal defense lawyers; Sound recording executives and producers; Trials (Murder); Legal drama; Spanish language materials; French language materials; Biographical films; Drama; Feature films; Fiction films; Legal films; Made-for-TV movies; Video recordings for the hearing impaired; Films biographiques; Films de fiction; Film; DVD-Video